KINERJA REFRIGERAN HCR-22 SEBAGAI PENGGANTI REFRIGERAN R-22 PADA SISTEM PENYEGARAN UDARA DOMESTIK KINERJA REFRIGERAN HCR-22 SEBAGAI PENGGANTI REFRIGERAN R-22 PADA SISTEM PENYEGARAN UDARA DOMESTIK - Piarah, Wahyu H. (Jurnal MEKANIKAL, 2010)
The purpose of this study is to analyze the performance of HCR-22 refrigerant as a subtitute  matter to R-22 refrigerant. The research methods is to test the influence of the usage of different refrigerant to the cooling length of the room, cooling effect, compressor work, the COP and refrigerant mass flow rate. The results show that HCR-22 refrigerant more quickly cool the room compared to R-22 refrigerant. Average cooling effect of HCR-22 refrigerant = 256,606 kJ/kg and R-22 refrigerant = 159.927 kJ / kg. Average working compressor of HCR-22 refrigerant = 60,334 kJ/kg and R-22 refrigerant= 25.361 kJ / kg;  COP of HCR-22 refrigerant = 4,141 and R-22 refrigerant = 6.306;  Mass flow rate of  HCR-22 refrigerant = 0,039kg / s and R-22 refrigerant = 0.062 kg / s.